Complement system biomarkers in epilepsy. (August 2018) - Kopczynska, Maja; Zelek, Wioleta M.; Vespa, Simone; Touchard, Samuel; Wardle, Mark; Loveless, Samantha; Thomas, Rhys H.; Hamandi, Khalid; Morgan, B. Paul
Highlights: Plasma complement biomarkers distinguish epilepsy patients from controls (area under the curve: 0.8). Plasma complement biomarkers differ between controlled and uncontrolled epilepsy patients. The data implicate complement dysregulation and inflammation in the pathogenesis of epilepsy. Abstract: Purpose: To explore whether complement dysregulation occurs in a routinely recruited clinical cohort of epilepsy patients, and whether complement biomarkers have potential to be used as markers of disease severity and seizure control. Methods: Plasma samples from 157 epilepsy cases (106 with focal seizures, 46 generalised seizures, 5 unclassified) and 54 controls were analysed. Concentrations of 10 complement analytes (C1q, C3, C4, factor B [FB], terminal complement complex [TCC], iC3b, factor H [FH], Clusterin [Clu], Properdin, C1 Inhibitor [C1Inh] plus C-reactive protein [CRP]) were measured using enzyme linked immunosorbent assay (ELISA). Univariate and multivariate statistical analysis were used to test whether combinations of complement analytes were predictive of epilepsy diagnoses and seizure occurrence. Correlation between number and type of anti-epileptic drugs (AED) and complement analytes was also performed. Results: We found: 1) significant differences between all epilepsy patients and controls for TCC (p < 0.01) and FH (p < 0.01) after performing univariate analysis. 2) multivariate analysis combining six analytes (C3, C4, Properdin, FH, C1Inh, Clu) to give a predictive value (area under the curve) of 0.80 for differentiating epilepsy from controls. 3) significant differences in complement levels between patients with controlled seizures (n = 65) in comparison with uncontrolled seizures (n = 87). Levels of iC3b, Properdin and Clu were decreased and levels of C4 were increased in patients with uncontrolled seizures. 4) no correlation was found between the level of complement biomarkers and the number of AEDs taken, but an association between some analyte levels and drug therapy was seen in patients taking sodium valproate, clobazam, and perampanel. Conclusion: This study adds to evidence implicating complement in pathogenesis of epilepsy and may allow the development of better therapeutics and prognostic markers in the future. Replication in a larger sample set is needed to validate the findings of the study.